FOOD CONSUMPTION AND NUTRITIONAL STATUS OF UNDERFIVE CHILDREN ON FISHERMEN’S FAMILY DURING MONETARY CRISIS PERIOD JUNE 1998-AUGUST 1999 SEMARANG MUNICIPALITY - Laksmi Widajanti; Martha Irene Kartasurya (JOURNAL OF COASTAL DEVELOPMENT, 2004)
Since late 1997 Indonesia has been overwhelmed by monetary crisis and low income communities including fishermen received the worst impact of it. This study was intended to see whether there was a difference in food consumption and the nutritional status of the underfive years old children in the fishermen community before and during the crisis. Sixty three subjects were chosen by cluster random sampling method and were followed from June 1998 to August 1999. Food consumption data were gathered by weighing method for two days and food frequency questionnaires. Paired t-test was used in the analysis. The study revealed that the families income almost doubled, the food consumption was significantly increased in term of energy and protein. It was found that children have more frequent meal per day and more varieties of food eaten daily. The children’s weight and height increased in an average of 2.5 kg and 8.7 cm, respectively. The nutritional status in aggregate data showed an increase in height per age but slightly decrease in weight per age and weight per height indices but not statistically significant. By group analysis, more children had lower nutritional status in all indices. It is concluded that there were improvement in food consumption of the underfive years old children, as the children grow older. However, their nutritional status became lower. The primary health care providers in the area should be informed on this situation. It is important that they should direct nutritional education program to improve the nutritional status of the children in its working area.